التقييم ‬‫المالي‬ ‫للمشاريع‬ ‫الستثمارية‬ ‫في‬ ‫ظل‬ ‫ظروف‬ ‫عدم‬ ‫التاكد‬ ‫دراسة‬ ‫حالة‬ ‫–‬ ‫مشروع ‬‫العجائن‬ ‫ل‫مؤسسة‬‫مطاحن‬ ‫بلغيث‬ ‫الكبرى‬ ‫خالل‬ ‫الفترة‬ ‫‪2016‬‬ ‫‪/‬‬ ‫‪2023‬‬ - ‫مريم ‫بن ‬‫خالد‬ ‬; ‬‫لبن ى‫ناصف ‬ (My University, 2019)
The study of the evaluation of investment projects is a tool important for strategic planning, and the key point in investment decision, i.e. when it comes to ndertaking the project (acceptance) or to refute it, this happens through the fact that it allows measure (identify) the resources and the amount of money eeded to establish and operate it sufficiently and over time suitable on the one hand, and recognize the income to be expected throughout throughout its irtual life on the other hand, the beginning of the study of the financial feasibility of the projects takes place after the study legal, environmental, as well as he marketable study then the study of the engineer. And after having acquired the information necessary to from these studies, comes from the financial study as the last step before the investment decision which estimates the flows cash flow in and out of the project, and determine its structure optimal financing nd ssessment of commercial profitability from the use of a set of standards and tools which vary according to the nature of the project and its circumstances of taking decision where we find circumstances for its total assurance, and the risk circumstances and the risk circumstances and another for the uncertainties. .............................................................. دراسة تقييم المشاريع الاستثمارية هي أداة مهمة للتخطيط الاستراتيجي، والنقطة الأساسية في قرار الاستثمار، أي عندما يتعلق الأمر بتنفيذ المشروع (القبول) أو دحضه، وذلك يكون من خلال ما يسمح به قياس (تحديد) الموارد ومبلغ الأموال اللازمة لإنشائها وتشغيلها بشكل كافي وعلى مدى الزمن مناسبة من ناحية، والتعرف على الدخل المتوقع طوال الوقت طوال حياتها الافتراضية من ناحية أخرى، بداية ويتم دراسة الجدوى المالية للمشاريع بعد الدراسة الدراسة القانونية والبيئية والتسويقية ثم الدراسةمن المهندس. وبعد الحصول على المعلومات اللازمة لذلك ومن هذه الدراسات يأتي من الدراسة المالية كأخيرة خطوة قبل قرار الاستثمار الذي يقدر التدفقات التدفق النقدي داخل وخارج المشروع، وتحديد هيكله التمويل الأمثل وتقييم الربحية التجارية من استخدام مجموعة من المعايير والأدوات التي تختلف حسب طبيعة المشروع وظروف اتخاذه القرار عندما نجد الظروف اللازمة لضمانه الكامل، و ظروف المخاطرة وظروف المخاطرة وغيرها لعدم اليقين.. ‬